Pola Konsumsi di Kota Surabaya Sebagai Indikator Peningkatan Kesejahteraan Masyarakat - Ully Prisandini; Arjunaidi Viky Rifandi; Muhammad Yasin (CiDEA Journal, 2023)
Prosperity is always the main target of every government. However, methods to measure prosperity are debatable. Several people argue that the poverty standard from United Nations is valid-enough to decide if people have fulfilled their needs. This measurement does not acknowledge that people also have wants and need to fulfill them. I decided to research Surabaya to understand the prosperity issues by using Purchasing Power Parity theory, the ability of people in Surabaya to fulfill their secondary wants by measuring the total marketing of housing and automobiles, and comparing the economic growth indicator of Surabaya.